The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1038/sj.bdj.2009.908
|View full text |Cite
|
Sign up to set email alerts
|

An audit of prosthodontics undertaken in general dental practice in the South East of England

Abstract: by a third. 4,5 There are certain unknown infl uences such as the changes to remuneration in general practice and the effect of increasing costs of dentistry on patients' choice on whether to restore or extract teeth. Therefore, the true long-term trend towards decreasing edentulism is not fully known but changes have occurred which might have an impact on healthcare delivery in the form of complete dentures.Before embarking upon changes in teaching it is important to identify what are the commonly practised a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
2
6
0
Order By: Relevance
“…These findings are similar to the findings of a survey conducted by Bartlett et al. (26) who found that in the south‐east of England, there were a low number of removable prostheses produced. They also found that few cobalt–chromium dentures were prescribed and that these were made in specialist private practice.…”
Section: Discussionsupporting
confidence: 91%
“…These findings are similar to the findings of a survey conducted by Bartlett et al. (26) who found that in the south‐east of England, there were a low number of removable prostheses produced. They also found that few cobalt–chromium dentures were prescribed and that these were made in specialist private practice.…”
Section: Discussionsupporting
confidence: 91%
“…A recent survey reported that 55% of Vocational Dental Practitioners and 71% of their trainers felt that the subject of FPDs had been 'poorly' or 'very poorly' covered at an undergraduate level (24). Furthermore, a recent examination of the provision of prosthodontic services in the South East of England indicates that many general dental practitioners are preferring to provide acrylic RPDs rather than FPDs, though this may be a reflection of costs involved in providing this treatment (9). These considerations suggest there is a potential for de-skilling within the dental profession in relation to FPDs.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is clear that changes in the funding system within the NHS in the UK and the current difficult financial climate mean that this expensive treatment option is being used less often. The long-term effect of this may lead to de-skilling and mean that access for patients to dentists who are comfortable providing FPDs will become more problematic (9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations